Creating and promoting awareness in breast cancer by the means of brochure. - Chan, Wan Ting. (2012)
Breast cancer is the most prevalent cancer among Singaporean women. In the present project, we aimed to raise breast cancer awareness in School of Biological Sciences for the purpose of educating and prevention. This project was a 3-member team effort. We used printed and digital medias with a common theme “Good Things come in Pair” to educate the students and staff from School of Biological Sciences. My individual task was the preparation of a six-page brochure. The brochure highlighted the lethal damages of breast cancer and the preventive measures to screen and reduce the risk of developing breast cancer. The display of the printed media was put up for an one month period at various locations at School of Biological Sciences. In addition, a two-day awareness campaign was carried out to raise the breast cancer awareness. Approximately 300 students and staff had support our campaign. A survey was done to evaluate the usefulness of the campaign. 97% of the respondents felt that they understood more about breast cancer after the breast cancer awareness campaign.